ОСОБЛИВОСТІ СТАНУ МАКРОЗООБЕНТОСУ ТИЛІГУЛЬСЬКОГО ЛИМАНУ (ПІВНІЧНЕ ПРИЧОРНОМОР’Я) У 2021 РОЦІ - Варігін, О.Ю. (Marine Ecological Journal, 2023)
The species composition and quantitative characteristics of the macrozoobenthos in the Tyligul estuary, located inthe northern Black Sea region 60 km northeast of the city of Odessa, were determined. The material was collected in May and September 2021 at 17 stations located in the form of sections that passed from one shore of the estuaryto the other. In the spring of 2021, 20 species of invertebrates belonging to the following taxa were identified as partof the macrozoobenthos community of the Tyligul estuary: Polychaeta – 4 species, Cumacea – 1, Isopoda – 2, Amphipoda –5, Gastropoda – 2, Bivalvia – 5, Chironomidae – 1. Amphipod crustaceans and bivalve molluscs each accounted for25% of all detected species. The most significant factor determining the species diversity and quantitative developmentof the macrozoobenthos of the estuary was the depth of the habitat of invertebrates, which varied from 1,5 to 13,5 mat different stations. The key species of the macrozoobenthos community of the Tyligul estuary were the bivalve molluscsMytilaster lineatus (Gmelin, 1791), Cerastoderma glaucum (Bruguiere, 1789) and Abra segmentum (Recluz, 1843).In the spring of 2021, the average abundance of M. lineatus was 25385±6803 ind.·m-2, which was 80,4% of the totalabundance of all macrozoobenthos, and the average biomass was 8525±1042 g·m-2 (75,2%). The invasive bivalve speciesArcuatula senhousia (Benson, 1842) was discovered for the first time at the station located near the exit of the channelconnecting the estuary with the sea. This opportunistic species can pose a serious threat to the development of the localbivalve Mytilaster lineatus. The autumn samples showed a substantial reduction in the quantitative parameters of benthicinvertebrates compared to the spring samples. In some areas of the estuary, the deadly phenomena led to the total deathof all benthic organisms. In general, in recent years, the species richness of the macrozoobenthos of the Tiligul estuaryhas decreased by three times compared to 1970–1980.